O caráter de Aurélia diante das mazelas sociais do séc. XIX - RODRIGUES, Conceição de França (2024)
This work aims to analyze the work Senhora, by José de Alencar, highlighting the criticism and contradictions present in Brazilian society in the 19th century, through his romantic work, which builds a female character who is educated to exercise autonomy as an individual. , thus being contradictory to the rigid upbringing of the other women of that period. In this sense, this article aims to analyze the trajectory of the protagonist Aurélia Camargo and her character, through her behavior in the face of the social ills of the 19th century, in order to identify the habits, customs and education of women in that society. Which thus demonstrates the predominance of the masculine over the feminine will and the fact that women were destined for a life of submission. We seek to discuss these relationships considering the female character and the context of the time, which is shaped by patriarchy and bourgeois education. It seeks to articulate with the themes of marriage, behavior, values ​​and submission the context of society. And so to investigate to what extent Aurélia's attitude and her character relate to each other, with the moral and social values ​​of the time, and what characteristics of an idealized woman she shows herself in the work.